On Alienation from the Built Environment. - Vogel, Steven (Ethical Theory & Moral Practice, 2014)
If 'environment' means 'that which environs us,' it isn't clear why environmentalist thinkers so often identify it with nature and not with the built environment that a quick glance around would reveal is what we're actually environed by. It's a familiar claim that we're 'alienated from nature,' but I argue that what we're really alienated from is the built environment itself. Typically talk of alienation from nature involves the claim that we fail to acknowledge nature's otherness, but the built environment is just as other from us as the natural one. And just as we are said to fail to recognize the role of nature as the origin of everything with which we have to do in the world, so too we fail to recognize the role of socially organized human labor in the objects that surround us. Overcoming alienation would require acknowledging the builtness and the sociality of the world we inhabit.